Health impact of electric discharge weapons: a review of case studies - Brasholt, Marie; Aon, Maha; Michaelsen, Lisa; Modvig, Jens (Torture Journal, 2024)
Introduction Electrical discharge weapons (EDWs) are increasingly used by law enforcement around the globe as a less lethal option to firearms. Concerns have been raised about their use, inter alia from the UN Committee Against Torture (UNCAT). The purpose of this manuscript is to provide an overview of case studies to assess the health consequences of EDW exposure. Methods Medline and Pubmed were searched for case studies on EDWs without restriction on language or date. Screening was first at abstract level and then at full article level. Articles were excluded if they were not case studies, concerned children under 15 years old or were off topic. A PRISMA flow diagram was created. Results A total of 71 studies were included, and they demonstrate a wide range of health consequences from minor injuries to lethal conditions. The injuries can be classified as direct and indirect, i.e., related to the use itself (e.g., penetration by darts) and related to falls and burns following neuromuscular incapacitation and ignition of flammable fluids. Cardiac incidents – some being fatal - were the health consequences found most reported, but the relation to the EDW is contested. In other cases, a very plausible association is established between EDW exposure and the health consequences. Description of pain and mental suffering related to EDW exposure was lacking in the reviewed case studies. Discussion EDWs may lead to physical and most likely mental suffering. When assessing patients and when documenting cases where persons may have been exposed to EDWs, including torture and ill-treatment cases, it is important to be aware of the different types of health consequences.